THE ’ATOMIC’ DESPATCH: FIELD MARSHAL AUCHINLECK, THE FALL OF THE TOBRUK GARRISON AND POST-WAR ANGLO-SOUTH AFRICAN RELATIONS - Stewart, Andrew (Scientia Militaria - South African Journal of Military Studies, 2011)
In January 1948, a despatch written by Field Marshal Sir Claude Auchinleck was published in London. These detailed military operations involving British Commonwealth forces had taken place between November 1941 and August 1942 in the Western Desert of North Africa. Initially submitted to the War Office (WO) five years before, a complex and often bitter political dispute helped ensure that the path of this despatch towards publication would prove a tortuous one. The key reason behind the delay was the South African government’s complaints about references to the Tobruk garrison, which, in June 1942, whilst under the command of a South African general, had been forced to surrender to German forces. The drafting of the despatch had begun almost as soon as the final battles had concluded. As a result of his reverses at the hands of General Erwin Rommel and the latter’s Afrika Korps, the then General Auchinleck had been dismissed by the British Prime Minister Winston Churchill in August 1942, during the so-called ‘Cairo Purge’, to be replaced by General Sir Harold Alexander. Alexander declined the offer of the newly created Persia and Iraq command and departed for India, where he later became Commander-in-Chief of the Indian Army, turning his focus to the completion of his account of recent events.